Identification of the factors related to the clinical knowledge sharing: A protocol for systematic review - Elaheh Mazaheri; Rahele Samouei; Mousa Alavi; Roya Kelishadi; Hasan Ashrafi-rizi (Wolters Kluwer Medknow Publications, 2022)
Today, the ability of the organizations to successfully knowledge management and sharing can help them in better performance. Effective knowledge sharing (KS) in the clinical context provides better clinical decisions and improves the quality of care services. This systematic review will be conducted to identify the factors related to the clinical KS (CKS). This systematic literature review will be conducted to search the published documents about the affecting factors on the (clinical) KS. To this end, PubMed, Scopus, Web of Science, ProQuest, Cochrane, Embase, SID, Magiran, IranDoc, and ISC will be thoroughly assessed with considered keywords and search strategy. No time limit will be considered and all relevant documents published will be evaluated until the start date of the search. To the best of our knowledge, no systematic review study has been conducted on the factors related to CKS and our research will try to comprehensively extract the effective factors in this topic. Identifying the factors affecting CKS will lead to transparency in the exchange and interpretation of clinical knowledge in clinical care delivery and making the best clinical decisions as well as improving the quality of clinical care. It will also provide a condition to facilitate the delivery of more effective clinical education for policymakers in the field of clinical education.